2013
DOI: 10.1123/rsj.37.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Student Employee Leadership Program: The Importance of Evaluating Effectiveness

Abstract: Outstanding student employees are essential for campus recreation programs to achieve organizational goals. To that end, this study examined the effectiveness of a leadership development program in which three groups of campus recreation (rec sports) student employees participated at various levels in the following: on-campus training, an off-site retreat, a scavenger hunt, and biweekly meetings. Using a quasi-experimental design, data were collected in two phases from 51 students and measured the growth of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
0
11
0
3
Order By: Relevance
“…Why not learn and advance leader development while enrolled as a student? Leader development researchers (Day et al 2014, Parks 2005, Tingle et al 2013) purport that leaders learn from experience, and purposeful deconstruction and reflection. They learn best when provided opportunities to lead, and from respected mentors who help them deconstruct and reflect upon their practices and outcomes.…”
Section: Contemporary Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Why not learn and advance leader development while enrolled as a student? Leader development researchers (Day et al 2014, Parks 2005, Tingle et al 2013) purport that leaders learn from experience, and purposeful deconstruction and reflection. They learn best when provided opportunities to lead, and from respected mentors who help them deconstruct and reflect upon their practices and outcomes.…”
Section: Contemporary Leadershipmentioning
confidence: 99%
“…Bennis and Thomas (2007) firmly concluded that leaders can be developed. Leadership scholars (Day et al 2014, Parks 2005, Tingle et al 2013 suggested that developing leaders need structured learning opportunities, experiences, mentoring, and reflection. Gardner (1995) suggested that leadership development programs must encourage developing leaders to understand that they need to present themselves as leaders.…”
Section: Leadership Development Literature Reviewmentioning
confidence: 99%
“…To measure growth of leadership capacity, Kouzes and Posner's (2006) Student Leadership Practices Inventory was used. The study found that by having student participate in a yearlong leadership training program, collegiate recreation professionals can create meaningful leadership programs (Tingle et al., ).…”
Section: Developing Student Employees’ Leadership Capacity Using Chicmentioning
confidence: 99%
“…The study tried to determine if significant differences in leadership development among three differing student employee groups existed based on training received in each group. The researchers created the Student Leadership Retreat Training (SLRT) program (Tingle et al., ). Students were divided into three groups: mentors, midlevel supervisors, and new hires.…”
Section: Developing Student Employees’ Leadership Capacity Using Chicmentioning
confidence: 99%
“…The Recreational Sports Journal (RSJ) contains numerous studies focusing on student learning (e.g., Danbert, Pivarnik, McNeil, & Washington, 2014;Hall, 2013) and student development (e.g., Simmons & Childers, 2013;Tingle, Cooney, Asbury, & Tate, 2013) in a variety of employment (e.g., aquatics) and participation settings (e.g., intramural sports). In the last 10 years, however, there have been only seven RSJ studies examining growth and professional development, or satisfaction among NIRSA professionals.…”
mentioning
confidence: 99%